2020
DOI: 10.1136/bmjopen-2020-042351
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance dispatch of older patients following primary and secondary telephone triage in metropolitan Melbourne, Australia: a retrospective cohort study

Abstract: BackgroundMost calls to ambulance result in emergency ambulance dispatch (direct dispatch) following primary telephone triage. Ambulance Victoria uses clinician-led secondary telephone triage for patients identified as low-acuity during primary triage to refer them to alternative care pathways; however, some are returned for ambulance dispatch (secondary dispatch). Older adult patients are frequent users of ambulance services; however, little is known about the appropriateness of subsequent secondary dispatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Alternatives could be considered by using secondary triage by community nurses or trained paramedics to perform a clinical assessment before transfer to the ED 42 . Indeed, in our study, more than half of the patients were transported by private ambulance, and it has been shown that training of paramedics and secondary triage after assessment could limit referrals to the ED 43,44 . Our study emphasized the importance of reinforcing primary care, particularly for older patients with numerous comorbidities (polymedication, cardiovascular comorbidity, fall‐related injury) for whom the risk of hospital‐acquired complications is highest and may be exacerbated in the busy context of the EDs 45…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Alternatives could be considered by using secondary triage by community nurses or trained paramedics to perform a clinical assessment before transfer to the ED 42 . Indeed, in our study, more than half of the patients were transported by private ambulance, and it has been shown that training of paramedics and secondary triage after assessment could limit referrals to the ED 43,44 . Our study emphasized the importance of reinforcing primary care, particularly for older patients with numerous comorbidities (polymedication, cardiovascular comorbidity, fall‐related injury) for whom the risk of hospital‐acquired complications is highest and may be exacerbated in the busy context of the EDs 45…”
Section: Discussionmentioning
confidence: 82%
“…42 Indeed, in our study, more than half of the patients were transported by private ambulance, and it has been shown that training of paramedics and secondary triage after assessment could limit referrals to the ED. 43,44 Our study emphasized the importance of reinforcing primary care, particularly for older patients with numerous comorbidities (polymedication, cardiovascular comorbidity, fallrelated injury) for whom the risk of hospital-acquired complications is highest and may be exacerbated in the busy context of the EDs. 45 To our knowledge, no previous study to date has investigated the training of medical dispatchers in conjunction with geriatricians to improve the dispatch procedure of older patients.…”
Section: Discussionmentioning
confidence: 93%
“…A/B dispatch: EMS dispatch with lights and siren. C/D dispatch: EMS dispatch without lights and siren 1 SpO2 < 95% for which the patient received bronchodilators; convulsion for which the patient received an anticonvulsant; allergic reaction for which the patient received epinephrine; any airway management, CPR or blood glucose < 4 for which the patient received IV glucose; SpCO > 5 for which the patient received oxygen; or overdosage or poisoning for which the patient received an antidote A/B dispatch and the patient did not receive any significant treatment 1 and was not transported with A/B priority C/D dispatch and no transport but the patient received significant treatment 1 C/D dispatch and transportation with A/B priority the Emergency Department if transported, transportation code and priority or non-transportation code. These records were then collected into a Microsoft Excel ® table to which the research assistants manually inputted additional data from the patient's EMS records (i.e., the patient's medical history, vital signs, and any treatment received), which were validated by the authors TS and KK.…”
Section: Table 1 Criteria For the Priority Assessment Of The Emergenc...mentioning
confidence: 99%
“…Author details 1 Tampere University of Applied Sciences, Kuntokatu 3, 33520 Tampere, Finland. 2 Centre for Prehospital Emergency Care, Emergency Medical Services, Wellbeing Services County of Pirkanmaa, Satakunnankatu 16, 33100 Tampere, Finland.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation